The impact of the COVID-19 pandemic on musculoskeletal disorders-related sick leave among healthcare workers: a retrospective analysis of Slovenian national data - Zerbo Šporin, Dorjana; Kozinc, Žiga; Prijon, Ticijana; Metličar, Tanja; Šarabon, Nejc (Frontiers in Public Health, 2025)
PurposeMusculoskeletal disorders (MSDs) are one of the main causes of health-related absenteeism. MSDs were a known problem among healthcare workers (HCWs) even before COVID-19. The pandemic, with its associated stresses and changes in working conditions, may have influenced the incidence and duration of MSDs-related sick leave (SL) among HCWs. The aim of this study was to compare the incidence and duration of MSDs-related SL among HCWs before and during the COVID-19 pandemic, with a focus on differences between age and gender groups.MethodsA retrospective analysis was conducted using Slovenian national SL data on work-related MSDs within NACE Rev. 2 “Human health activities” for 2019, 2020, and 2021, categorized by gender and age.ResultsThe study found that older HCWs, particularly women, consistently had a higher incidence of work-related MSDs SL than their younger counterparts. However, during the pandemic, MSDs were more common among younger men, while the average duration of SL was longer among younger women. On the other hand, in older HCWs, the average SL incidence decreased during the pandemic, while the SL duration substantially increased.ConclusionThe dynamics of MSDs related SL among HCWs are complex and influenced by several factors, including the challenges posed by the COVID-19 pandemic. Healthcare managers should implement tailored strategies to address MSDs-related absenteeism among specific groups of HCWs to promote a healthier workforce and ensure a resilient healthcare system during health crises.